Effects of a Savoring Intervention on Resilience and Well-Being of Older Adults. (January 2019) - Smith, Jennifer L.; Hanni, Agnieszka A.
Savoring is the ability to be mindful of positive experiences and to be aware of and regulate positive feelings about these experiences. Previous research has found that savoring interventions can be effective at improving well-being of younger adults, but findings have not been extended to older populations. This pilot study examined the effects of a 1-week savoring intervention on older adults' psychological resilience and well-being (i.e., depressive symptoms and happiness). Participants, 111 adults ages 60 or over, completed measures of resilience, depressive symptoms, and happiness pre- and postintervention as well as 1 month and 3 months after the intervention. Analyses revealed that participants who completed the savoring intervention with high fidelity also reported improvements in resilience, depressive symptoms, and happiness over time. These findings suggest that the savoring intervention has the potential to enhance older adults' resilience and psychological well-being.